The Implementation of Indonesian Realistic Mathematics Education (PMRI) on Learning Outcomes and Learning Activities in ZISWAF in Grade VIII of State Islamic Junior High School (MTsN) 2 Pontianak City - Muahamad Firdaus; Syahruddin Usman; Erwin Hafid; Arnadi (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2025)
This study aims to analyze the extent of improvement in student learning outcomes through instruction that does not apply Indonesian Realistic Mathematics Education (PMRI) on ZISWAF material, the significance of learning outcome improvement through PMRI-based learning, the differences between both approaches, and the level of student activity in participating in PMRI-based learning in class VIII of Madrasah Tsanawiyah Negeri (MTsN) 2 Pontianak City. The research employed a quantitative approach with a True Experimental design, specifically using the Randomized Pretest-Posttest Control Group Design. Data were collected through indirect communication techniques using a learning activity questionnaire and through measurement techniques involving essay tests on ZISWAF material. The research sample consisted of students from classes VIII A and VIII B, selected randomly. The findings indicate that students' learning outcomes after receiving non-PMRI-based instruction showed improvement compared to their pretest scores. Furthermore, students who were taught using the PMRI approach exhibited significantly better learning outcomes than before treatment. A comparison between both groups revealed that students who received PMRI-based learning achieved higher posttest scores than those who did not. Additionally, as many as 24 students (67%) demonstrated high to moderate levels of learning activity during PMRI-based ZISWAF instruction. The implementation of PMRI in teaching ZISWAF significantly enhances both cognitive outcomes and student engagement. These findings support the integration of contextual and realistic mathematics learning in Islamic education to foster deeper understanding and active learning behavior.